The Experiences and Perceptions of Street-Involved Youth Regarding Emergency Department Services. (May 2016) - Nicholas, David B.; Newton, Amanda S.; Calhoun, Avery; Dong, Kathryn; deJong-Berg, Margaret A.; Hamilton, Faye; Kilmer, Christopher; McLaughlin, Anne Marie; Shankar, Janki
Street-involved (SI) youth comprise a substantial component of the urban homeless population. Despite being significant users of hospital emergency department (ED) services for acute and ongoing health needs, little is known about their experiences of ED care and the factors affecting their ED use. This study used a grounded theory and community-based approach to examine these issues. Focus groups and individual interviews were facilitated with 48 SI youth between ages 15 and 26 years, recruited in hospital or through community agencies serving SI youth in a major Western Canadian city. Results demonstrate that SI youth often perceived suboptimal care and experienced long waiting periods that led to many avoiding or prematurely exiting the ED. Service gaps appeared to have a negative bearing on their care and health outcomes. Findings invite a critical review of ED care processes, structures, and staff interactions in the aim of enhancing ED services to SI youth.